The mediating effect of serum cortisol between stigma and post-stroke depression in stroke patients - Gong, Shitong; Wang, Shiyan; Wang, Jiangbo; Yin, Yiming; Wu, Yihao (Frontiers in Public Health, 2025)
ObjectiveThis study aimed to explore the mediating effect of serum cortisol on the relationship between stigma and post-stroke depression (PSD) in patients with acute ischemic stroke. To enhance early screening for post-stroke depression and prevent its development.MethodsA total of 367 patients admitted to the Department of Neurology and Neurosurgery at Xuzhou Central Hospital between January and December 2024 were selected using a convenience sampling method. Participants completed a general information questionnaire and the 8-item Stigma Scale for Chronic Illness, and their serum cortisol levels were measured at 8:00 a.m. the day after admission. Spearman correlation was used to analyze the correlation between serum cortisol, stigma level and depression degree in patients with acute ischemic stroke. The mediating effect Model was tested by Model 4 model in the PROCESS plug-in.ResultsAmong the participants, 182 were in the PSD group and 185 in the non-PSD group, with significant differences in income, education, serum cortisol, and stigma levels between the groups (p < 0.05). Spearman correlation analysis showed a significant positive correlation between stigma and depression severity (r = 0.715, p < 0.001), stigma and serum cortisol (r = 0.193, p < 0.001), and serum cortisol and depression severity (r = 0.261, p < 0.001). Mediation analysis using Model 4 of the PROCESS macro indicated that serum cortisol partially mediated the relationship between stigma and depression, with a mediating effect size of 0.019 (95%CI: 0.004–0.046), accounting for 2.5% of the total effect.ConclusionThese findings suggest that serum cortisol plays a partial mediating role between stigma and PSD in patients with acute ischemic stroke, highlighting a potential biological mechanism linking psychosocial stress to mental health outcomes in this population.